Axial Spondyloarthritis: Mimics and Pitfalls of Imaging Assessment - Caetano, António Proença; Mascarenhas, Vasco V.; Machado, Pedro M. (Frontiers in Medicine, 2021)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disorder that predominantly involves the axial skeleton. Imaging findings of axSpA can be divided into active changes, which include bone marrow edema, synovitis, enthesitis, capsulitis, and intra-articular effusion, and structural changes, which include erosions, sclerosis, bone fatty infiltration, fat deposition in an erosion cavity, and bone bridging or ankylosis. The ability to distinguish between imaging lesions suggestive of axSpA and artifacts or lesions suggestive of other disorders is critical for the accurate diagnosis of axSpA. Diagnosis may be challenging, particularly in early-stage disease and magnetic resonance imaging (MRI) plays a key role in the detection of subtle or inflammatory changes. MRI also allows the detection of structural changes in the subchondral bone marrow that are not visible on conventional radiography and is of prognostic and monitoring value. However, bone structural changes are more accurately depicted using computed tomography. Conventional radiography, on the other hand, has limitations, but it is easily accessible and may provide insight on gross changes as well as rule out other pathological features of the axial skeleton. This review outlines the imaging evaluation of axSpA with a focus on imaging mimics and potential pitfalls when assessing the axial skeleton.